The wonderful UNESCO collection of Panji tales in Leiden University Libraries - Tol, Roger (UI Scholars Hub, 2019)
Leiden University Libraries houses the greatest collection of Panji manuscripts in the world. This became evident while preparing the successful nomination of Panji tales manuscripts for UNESCO’s Memory of the World Programme. This article begins with observations on Panji tales in general. They originated in East Java and have subsequently spread to other areas in Southeast Asia. This is followed by a description of the collection’s composition and its history. The collection exists of over 260 manuscripts in eight languages, the majority of manuscripts written on palm leaf or paper. I have described four manuscripts in detail paying special attention to their provenance and history. Originating from four locations, written in four languages in three different scripts, they can be considered representative of the collection. A complete listing of all manuscripts is given in the appendix.